Measuring child coping in times of societal crises: Pilot development, reliability, as well as mental health and meaning mindset convergent validity of the children’s crisis coping scale (3Cs) - Armstrong, Laura L.; Potter, Catherine L. (Frontiers in Psychology, 2022)
To date, there are no brief child self-report coping measures for the pandemic and other major societal events resulting in social or learning disruptions for children. Ignoring the voice of children can ultimately result in programs or services that fail to meet their needs. Thus, a child self-report measure called the 3Cs (Children’s Crisis Coping) was developed and underwent pilot evaluation. This measure was designed in collaboration with key stakeholders using a Knowledge Translation-Integrated development framework. Some of the primary concerns that were relevant in the literature for the development of a pandemic coping measure included stress, worries, loneliness, and unpredictable school changes. The completed 4-item measure, grounded in these concerns, demonstrated good internal consistency reliability, as well as convergent validity with mental health and meaning mindset. A Second Wave Positive Psychology framework is presented concerning a spiritual concept called "meaning mindset" and it’s association with positive societal crisis coping (i.e., pandemic coping in the present study).